Transcendental Philosophy as a Scientific Research Programme - Lewin M. (Кантовский сборник, 2021)
Transcendental philosophy was not born like Athena out of Zeus’s head, mature and in full armour from the very beginning. That is why in both prefaces to the Critique of Pure Reason (1781 and 1787) Kant introduces the concept of transcendental philosophy as an “idea.” The idea understood architectonically develops slowly and only gradually acquires a definite form. As witnessed by the works of Kant himself and of his predecessors and followers, the idea of transcendental philosophy has undergone a series of changes and adjustments compared to the initial plan. In this context, my goal is not simply exegesis and historical investigation of transcendental philosophy, but also to look at it from a systematic and methodological perspective. I examine the concept of transcendental philosophy from the viewpoint of programmatic metaphilosophy. The first part discusses programmatics as a distinct subsection of metaphilosophy. I argue that Kant’s architectonic methodology and the methodology of Lakatos can be used to understand the inception, development and degradation of philosophical systems. In the second part I look at the project of transcendental philosophy and the stages of its development from the standpoint of architectonics. The third part shows that Lakatos’s methodology can provide a detailed insight into the elements of transcendental philosophy, a clear idea of its logic and identify the component parts that can be improved and developed. In spite of the different levels of detailing and epistemological prerequisites, the methodologies of Kant and Lakatos can be combined to achieve a metaphilosophically informed and progressive understanding of philosophical projects.